Program Persiapan Peralihan Penggunaan Kompor Induksi dari Kompor Gas (LPG) di Desa Sandik Kecatan Batulayar Kabupaten Lombok Barat - Sultan, Sultan; Nrartha, I Made Ari; Mulijono, Agung Budi; Sasongko, Sudi Maryanto Al; Ginarsa, I Made; Widianty, Desi; Yadnya, Made Sutha (Jurnal Gema Ngabdi, 2025)
The induction stove transition program in Sandik Village, Batulayar District, West Lombok Regency, was initiated to support the government's push for more efficient and eco-friendly energy use. Despite the benefits of induction stoves-such as energy efficiency, safety, and environmental advantages-LPG remains the dominant cooking fuel due to limited public awareness. The program involved education, practical demonstrations, and efficiency comparisons between induction and gas stoves, while also identifying challenges like limited household electricity and entrenched cooking habits. Evaluation results show improved community understanding and operational skills, along with increased awareness of clean energy transitions. This initiative strengthens the community’s readiness to adopt induction stoves and offers a replicable model to support sustainable energy policies in other regions.